Guerrilla Marketing: A Theoretical Review - P. B., Sajoy (Indian Journal of Marketing, 2013)
Guerrilla marketing, in spite of its modest beginnings in the early 1960s, is today extensively used not just by small and medium enterprises, but also by big corporations. Guerrilla marketing, with its unique characteristic of surprise, diffusion and low cost has come to stay because of these advantages over traditional marketing. Over the years, numerous methods of guerrilla marketing have emerged. The most popular of them are Ambient marketing, Sensation marketing, Viral marketing, Buzz marketing and Ambush marketing. Despite its numerous advantages, guerrilla marketing suffers from some negatives, which have to be accounted before any guerrilla marketing campaign is conducted. The present paper discusses the aforementioned aspects of Guerrilla Marketing.